Potential Security Issues in Implementing IaaS and PaaS Cloud Service Models - Erlangga, Wishnu Kusumo Agung; Ramadhan, Muhammad Rheza (Universitas Komputer Indonesia, 2022)
As the digital world evolves, so does potential problem that computer users encounter. Cybersecurity threats are still evolving and expanding. Unfortunately, most computer users do not understand this properly. The cloud models offered by various public cloud providers remain concentrated on infrastructure resources, application platforms, and software services despite the recent increase in the popularity of cloud computing. The first step in this study will be a literature review to get an understanding of accessible cloud service models. The papers chosen for the study spans 2010 to 2020. All data was gathered from pertinent and related literature on cyber security and cloud computing. The following tenets serve as the foundation for this architecture. First, in the described architecture, the perimeter scanner serves as the first entry point for external cyberattacks. Firewall and other security layers become next barriers if the attack can get past first layer. On the other side, the machine learning system will detect every successful assault that gets past the security layers. As a result, there are numerous viewpoints and categorization systems for diverse attacks. It is possible to advance cyber security research in the context of cloud technology by merging the results of existing studies and developing international guiding standards